Early life microbial succession in the gut follows common patterns in humans across the globe - Guilherme Fahur Bottino; Kevin S. Bonham; Fadheela Patel; Shelley McCann; Michal Zieff; Nathalia Naspolini; Daniel Ho; Theo Portlock; Raphaela Joos; Firas S. Midani; Paulo Schüroff; Anubhav Das; et al. (Nature Communications)
Abstract Characterizing the dynamics of microbial community succession in the infant gut microbiome is crucial for understanding child health and development, but no normative model currently exists. Here, we estimate child age using gut microbial taxonomic relative abundances from metagenomes, with high temporal resolution (±3 months) for the first 1.5 years of life. Using 3154 samples from 1827 infants across 12 countries, we trained a random forest model, achieving a root mean square error of 2.56 months. We identified key taxonomic predictors of age, including declines in Bifidobacterium spp. and increases in Faecalibacterium prausnitzii and Lachnospiraceae. Microbial succession patterns are conserved across infants from diverse human populations, suggesting universal developmental trajectories. Functional analysis confirmed trends in key microbial genes involved in feeding transitions and dietary exposures. This model provides a normative benchmark of “microbiome age” for assessing early gut maturation that may be used alongside other measures of child development.